Local Journalism in the Shadow of the Federal City - Dasgupta, Sunil; Farkas, Jennifer; Rasicot, Jule (I Hate Politics Podcast, 2025)
Bethesda Magazine and its news website Bethesda Today refocus on their core market as a new federal administration seeks to remake the Washington DC metropolitan area. Sunil Dasgupta talks with publisher Jennifer Farkas and editor Jule Rasicot about the road ahead for local journalism in Bethesda and Montgomery County, MD. Newly in public domain music by Clara Smith and The Troubadours.
Keywords: I Hate Politics; I Hate Politics